2019
DOI: 10.3390/antiox8040096
|View full text |Cite
|
Sign up to set email alerts
|

Water- and Fat-Soluble Antioxidants in Human Seminal Plasma and Serum of Fertile Males

Abstract: Reactive oxygen species (ROS) are physiologically involved in functions like sperm maturation, capacitation and acrosome reaction, but their excess is involved in male infertility. Antioxidants in seminal plasma (SP) are an important factor balancing physiologic and harmful ROS activities. In this study, we determined and compared the full profiles of the water- and fat-soluble antioxidants in SP and serum of 15 healthy fertile subjects (ranging between the ages of 35 and 42 years). Ejaculates were obtained af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 58 publications
2
51
0
1
Order By: Relevance
“…Confirming the results in unsorted sperms in human (Lazzarino et al, 2019), rooster (Min, Sun, Niu, & Liu, 2016) and bull (Paudel et al, 2010), the present study showed that VC significantly reduced the MDA levels in sex-sorted bull sperm (Figure 1a). VC can scavenge ROS directly as one kind of antioxidant (Attia, Hassan, & Qota, 2009) and effectively improve levels of endogenous antioxidants (catalase and glutathione) in sperm (Hu et al, 2010), which explains the lower MDA levels in VC-treated groups.…”
Section: Discussionsupporting
confidence: 89%
“…Confirming the results in unsorted sperms in human (Lazzarino et al, 2019), rooster (Min, Sun, Niu, & Liu, 2016) and bull (Paudel et al, 2010), the present study showed that VC significantly reduced the MDA levels in sex-sorted bull sperm (Figure 1a). VC can scavenge ROS directly as one kind of antioxidant (Attia, Hassan, & Qota, 2009) and effectively improve levels of endogenous antioxidants (catalase and glutathione) in sperm (Hu et al, 2010), which explains the lower MDA levels in VC-treated groups.…”
Section: Discussionsupporting
confidence: 89%
“…As a biological response to oxidative stress, seminal plasma has evolved one of the most powerful antioxidant fluids known to man, replete with a range of antioxidant enzymes and small molecular mass free radical scavengers that, combined, generate a level of total antioxidant power that is estimated to be 10× higher than blood [56]. This antioxidant cocktail includes catalase, superoxide dismutase (SOD), glutathione peroxidase, glutathione-S-transferase and peroxiredoxins as well as water-soluble (uric acid, hypotaurine, tyrosine, polyphenols, vitamin C, ergothionine and glutathione) and fat-soluble (all-trans-retinoic acid, all-trans-retinol, α-tocopherol, carotenoids and coenzyme Q10) scavengers [56][57][58].…”
Section: Inadequate Antioxidant Protection From Seminal Plasmamentioning
confidence: 99%
“…This tendency is certainly due to different reasons, including the lack of standardized, clearly effective pharmacological approaches of TBI patients, the increased knowledge of the molecular mechanisms underlying cerebral damage after TBI, and the lack of unwanted side effects for the large majority of low molecular weight antioxidants. With the exclusion of reduced glutathione (GSH), uric acid, and coenzyme Q10 (these last two are secondary antioxidants since this is not their primary biological role), another common characteristic of low molecular weight antioxidants is that mammals are unable to perform their synthesis so that they depend on regular intake with diet to have adequate circulating and tissue concentrations of antioxidants [47]. Therefore, the quality of food consumed and/or supplementation of adjuvants and nutraceuticals is of fundamental importance in order to provide significant protection in the case of increased ROS and RNS formation [48,49].…”
Section: Tbi and Oxidative/nitrosative Stress: A Rationale For Antioxmentioning
confidence: 99%
“…Efficient absorption of this molecule mainly occurs through the SVCT1 Na + -ascorbic acid transporter activity [54,55]. Although, circulating levels of AA are relatively low (30 to 70 mol/L serum in healthy humans) [47], abundant AA concentrations are found in peripheral tissues, particularly in the brain, where it is usually present in concentrations up to 3000 mol/L brain water [56][57][58]. The SVCT2 Na + -ascorbic acid transporter, ubiquitously distributed on the cell membrane of the different tissues, provides the electrogenic AA transport exploiting the favorable extracellular/intracellular sodium gradient [59,60].…”
Section: Ascorbic Acid (Vitamin C)mentioning
confidence: 99%